A Correlation Analysis of Knowledge, Experience, Religious Belief, and Behavior of Malaysian EPF Investors Towards Investing in Islamic and Conventional Unit Trusts - Md Abu Hasnat; Mohammed Monzurul Islam; Ziauddin Rahimi; Hüseyin Dağlı (Türkiye İslam İktisadı Dergisi)
The objective of the study is to examine the relationship between knowledge, religiosity and experience, and the behavior of employee provident fund (EPF) investors investing in Islamic and conventional unit trusts. The variables are extracted from the literature to achieve the objective. Additionally, 125 valid responses were composed through surveys of Malaysian government and private employees. The Statistical Package for Social Sciences has been applied to analyze the collected data, using correlation analysis techniques. This research found that knowledge about Islamic unit trusts and religious beliefs have a positive significant relationship with the EPF investors’ behavior of investing in Islamic unit trusts. Moreover, the experience of investing in Islamic and conventional unit trusts is also positively and significantly associated with the EPF investors’ behavior of investing in Islamic and conventional unit trusts, respectively. As research in this area is insufficient, this study will play a vital role for the unit trust industry in exploiting the financial strategies that are highly and positively observed by Malaysian EPF investors.